2009
DOI: 10.1080/08870440902939857
|View full text |Cite
|
Sign up to set email alerts
|

Planning bridges the intention–behaviour gap: Age makes a difference and strategy use explains why

Abstract: These findings suggest differential mechanisms in behaviour regulation in young and middle-aged individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 45 publications
5
64
5
Order By: Relevance
“…These findings suggest that when CR patients become motivated to engage in physical exercise, their intentions were not directly translated into action. This result is in line with Reuter et al [53] who found that planning is necessary to bridge the intention-behavior gap, but stands in contrast with research conducted by Renner et al [51] and Caudroit et al [52] among older individuals where intentions directly translated into action without preparatory strategies of approaching the activity.…”
Section: Tablesupporting
confidence: 76%
“…These findings suggest that when CR patients become motivated to engage in physical exercise, their intentions were not directly translated into action. This result is in line with Reuter et al [53] who found that planning is necessary to bridge the intention-behavior gap, but stands in contrast with research conducted by Renner et al [51] and Caudroit et al [52] among older individuals where intentions directly translated into action without preparatory strategies of approaching the activity.…”
Section: Tablesupporting
confidence: 76%
“…In the action phase, individuals face the difficulty to deal with setbacks and lapses by drawing upon their recovery self-efficacy . Previous literature also demonstrates the importance of self-efficacy and planning skills for physical activity in older adults (Renner, Spivak, Kwon, & Schwarzer, 2007;Reuter et al, 2010;Scholz et al, 2005;Sniehotta et al, 2005;Warner et al, 2014;Wolff, Warner, Ziegelmann, Wurm, & Kliegel, 2016;Ziegelmann & Lippke, 2007).…”
Section: Post-motivational Self-regulatory Constructs and Physical Acmentioning
confidence: 92%
“…For health behaviors, planning and the prioritization of goals seem to be of great importance (Gollwitzer, 1993;Lippke, Wienert, Kuhlmann, Fink, & Hambrecht, 2015;Reuter et al, 2010;Wiedemann, Lippke, Reuter, Ziegelmann, & Schüz, 2011). Research in self-regulatory planning strategies in relation to subjective physical age and physical activity might also be of interest for future research, especially considering the given results of planning as a predictor for physical activity in the final model.…”
Section: Implications and Conclusionmentioning
confidence: 99%